Emotional Eating in Young Athletes: Roles of Emotion Regulation and Gender as Moderating Factors (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2025)
The ability to regulate emotions is crucial for an athlete psychological well-being and performance. Poor emotional regulation may lead to maladaptive behaviors, such as emotional eating—a pattern of food consumption driven by negative emotions. Young athletes experience intense pressure from training, competition, and academic aspects, increasing the risk of emotional eating. This behavior affects not only their physical health but also their endurance and overall performance. This study aimed to examine the effect of emotion regulation on emotional eating in young athletes and the role of gender as the moderating variable. A quantitative approach was used with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis via SmartPLS software. Data were collected using questionnaires filled out by 82 young athletes, measuring emotion regulation using IERQ4S and emotional eating based on Van Strien's theory. In this study, accidental sampling was used. The results indicated that emotion regulation negatively affected emotional eating, meaning that better emotion regulation is associated with lower emotional eating tendencies. However, gender did not have a significant effect, either directly or as a moderator. These findings emphasize the importance of emotion regulation in preventing emotional eating in young athletes. The results of the study can be used to design interventions to strengthen emotion regulation, such as Acceptance and Commitment Therapy (ACT) and mindfulness-based approaches, and to support well-being and performance of athletes in training programs. Further research is needed to examine other factors, such as anxiety and stress in emotional eating behavior in young athletes, with a more diverse sample coverage in terms of sport types and age range to enrich understanding.